2008
DOI: 10.1063/1.2975339
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission, resonant photoemission, and x-ray absorption of a Ru(II) complex adsorbed on rutile TiO2(110) prepared by in situ electrospray deposition

Abstract: An experimental study of the bonding geometry and electronic coupling of cis-bis(isothiocyanato)bis(2,2(')-bipyridyl-4,4(')-dicarboxylato)-ruthenium(II) (N3) adsorbed on rutile TiO(2)(110) is presented, along with supporting theoretical calculations of the bonding geometry. Samples were prepared in situ using ultrahigh vacuum electrospray deposition. Core-level photoemission spectroscopy was used to characterize the system and to deduce the nature of the molecule-surface bonding. Valence band photoemission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
173
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 86 publications
(185 citation statements)
references
References 45 publications
11
173
1
Order By: Relevance
“…16 On TiO 2 N3 has shown bonding via de-protonation of two carboxylic acid groups on the bi-isonicotinic acid ligand, and via the interaction of sulphur on the thiocyanate ligand. 17 Since the surface in this experiment is oxygen terminated it is expected that N3 will form chemical bonds with the surface in a manner similar to that seen on TiO 2 . 17 We have also previously reported the charge transfer interaction of N3 and its bi-isonicotinic acid ligand on Au(111) 18,19 and N3 as well as related water splitting molecules on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 On TiO 2 N3 has shown bonding via de-protonation of two carboxylic acid groups on the bi-isonicotinic acid ligand, and via the interaction of sulphur on the thiocyanate ligand. 17 Since the surface in this experiment is oxygen terminated it is expected that N3 will form chemical bonds with the surface in a manner similar to that seen on TiO 2 . 17 We have also previously reported the charge transfer interaction of N3 and its bi-isonicotinic acid ligand on Au(111) 18,19 and N3 as well as related water splitting molecules on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…17 Since the surface in this experiment is oxygen terminated it is expected that N3 will form chemical bonds with the surface in a manner similar to that seen on TiO 2 . 17 We have also previously reported the charge transfer interaction of N3 and its bi-isonicotinic acid ligand on Au(111) 18,19 and N3 as well as related water splitting molecules on TiO 2 . 17,20,21 The upper limit for the charge transfer time from N3 to Au(111) and TiO 2 was 4.4 fs 18 and 12 fs, 20 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1) on an Au(111) surface with coverages ranging from submonolayer to multilayers. It has recently been shown that UHV-ESD and related spray techniques provide a viable method for the transfer of non-volatile/thermally labile species such as dye molecules and polymers from solution onto surfaces held in UHV [33][34][35][36][37][38][39] ; the development and application of this technique is crucial for the deposition of Mn 12 (acetate) 16 . Images of the adsorbed Mn 12 (acetate) 16 are acquired using an STM operating at room temperature under UHV conditions.…”
mentioning
confidence: 99%
“…1 organometallic complexes to the dyes themselves to probe the charge transfer dynamics on the femtosecond timescale. [8][9][10] As pointed out by Brühwiler et al, 4 resonant inelastic x-ray scattering (RIXS) offers a similar potential for observing the charge transfer dynamics of adsorbed molecules as RPES.…”
Section: Introductionmentioning
confidence: 99%